Pathogens in patients with granulomatous lobular mastitis. (April 2019) - Wang, Jiachuan; Xu, Hua; Li, Zhixin; Li, Fang; Yang, Ye; Yu, Xuewen; Jiang, Dan; Xing, Li; Sun, Huili; Shao, Mumin
Highlights: Up to 95% of granulomatous lobular mastitis specimens had pathogens. Pathogens in GLM included bacteria, fungi and Mycobacterium tuberculosis complex groups. Most GLM patients (about 76.9%) had multiple pathogens as detected by next-generation sequencing(NGS)technology. The sensitivity and specificity of NGS method were significantly higher than those of traditional histochemical staining. Abstract: Objective: Granulomatous lobular mastitis (GLM) is a rare inflammatory disease of the breast that clinically mimics breast cancer. However, its etiology is not completely defined. The purpose of this study was to systematically study the bacteriology of GLM using advanced detection technology. Methods: Paraffin-embedded tissue from patients with GLM was collected. DNA was extracted from the samples and analyzed using next-generation sequencing (NGS) technology, and the data were processed using bioinformatics analyses. Results: A total of 40 patients were recruited into the study. A bioinformatics analysis revealed that a total of 17 genera or 19 species of pathogens were present in 39 of the GLM patients (97.5%). These included bacteria, fungi, and Mycobacterium tuberculosis complex group. Bacteria were found in 39 of the patient cases, while fungi were present in five. Only one case tested positive for M. tuberculosis complex. In addition, a single genus of pathogen was found in nine patients (23.1%), whereas 30 patients (76.9%) tested positive for multiple pathogens. Conclusions: This study profiled the microbiota of patients with GLM using NGS technology, which provides more useful information for establishing patient treatment plans.